A facile synthesis strategy of fungi-derived porous carbon-based iron oxides composite for asymmetric supercapacitors. Issue 7 (1st April 2022) - Zhao, Shanhai; Zheng, Ke; Zhang, Zhifang; Wang, Haibing; Ren, Junfeng; Li, Huiyu; Jiang, Feng; Liu, Yongsheng; Cao, Haijing; Fang, Zebo; Zhu, Yanyan
Abstract: Transition metal oxides (TMOs) have been considered as potential anode materials for asymmetric supercapacitors due to their high theoretical capacities. However, undesirable electric conductivity limits the further application in future energy storage. Here, a honeycomb-like architecture of FeOx embedded in the fungi-derived porous carbon-based material (FeOx/C) for asymmetric supercapacitor was reported. The facile synthesis strategy of fungi-derived porous carbon-based iron oxides was using the carbon derived from fungi and the process of carbothermal reduction to form the iron oxide compound. This carbon-encapsulated iron oxide compound provides highly specific surface area (The specific surface area of Fe–O–C-650 was largest (up to 219.0905 m 2 /g) compared with samples of Fe–O–C-550(144.0304 m 2 /g), Fe–O–C-750(201.7352 m 2 /g), Fe–O–C-850(163.2206 m 2 /g).), an abundance of redox sites, sufficient efficient channels for fast transportation of ions, excellent electrical conductivity, and stable skeleton. Under the three-electrode test system, the FeOx/C electrode delivers excellent specific capacitance of 565F/g at 1 mV/s and impressive cycling performance with capacitance retention of 100% after 3000 cycles. And the NiO electrode delivers a high specific capacitance of 425 F/g at a high current density of 5 mV/s. In addition, the FeOx/C//NiO asymmetric supercapacitor was assembled which exhibits remarkable specific capacitance of 111F/g at 10 mV/s and gravimetric energy density of 36 Wh/kg as well as gravimetric power density of 800W/kg with capacitance retention of 100% after 20, 000 cycles, approaching those of ions capacitors.